The Effect of The Wordwall Educational Game on Students’ Mathematical Understanding of Integer Addition and Subtraction - Hairunnisa, Zazkia; Badjeber, Rafiq; Elfira, Riska (FKIP Universitas Wisnuwardhana, 2026)
Students’ understanding of integer addition and subtraction at the junior high school level is still limited, even though these topics are fundamental in mathematics. Engaging learning media, such as the educational game Wordwall, is believed to support a more effective mathematical understanding. This study aims to examine the effect of the Wordwall educational game on students’ mathematical understanding. The method used in this research is a quasi-experimental design with a nonequivalent control group design. The research population consisted of seventh-grade students at SMP Negeri 3 Palu, with two classes selected as the sample: Class VII I as the experimental group and Class VII K as the control group. Data were collected through mathematical understanding tests that had met the standards of validity and reliability. The results indicate that the use of the Wordwall educational game enhances student engagement and participation; however, no significant difference was found between the experimental and control classes in terms of mathematical understanding. The Mann–Whitney U test yielded a p-value of 0.644, which is greater than the significance level (p > 0.05). This is believed to be influenced by differences in students’ prior knowledge, the relatively short duration of the media’s use, and the media’s lack of suitability for visualizing mathematical concepts. Consequently, the use of Wordwall did not have a significant effect on students’ mathematical understanding of integer addition and subtraction.